SOLID DOMICILIARY RESIDUES: CHARACTERIZATION AND ENERGY ESTIMATION FOR THE CITY OF CHIMBOTE - Quillos Ruiz, Serapio A. (2020)
The management and final disposal of Residential Solid Waste (RSD) present challenges and, at the same time, opportunities for the developing countries, and with little scientifictechnological progress in this area. In this work, the characterization of the RSD was evaluated to estimate the energy potential contained in the Residential Solid Organic Residues (RSOD) of the city of Chimbote. The study sample consisted of 60 dwellings, distributed into three socioeconomic levels, as established by the statistical methodology of the Ministry of the Environment of Peru. Thus, a per capita generation of RSD of 0.425 kg/person/day was obtained, where the RSOD represent 69.03 % (0.297 kg/person/day) of the RSD. Based on these results, the total of the RSOD reaches 69.8 tons/day. Finally, an evaluation was carried out to estimate the energy recovery contained in the RSOD through incineration, obtaining a generation of 15.33 MW by 2017, a situation that would represent an increase of 8 % during the decade 2017-27. Recovering the energy contained in the RSOD can contribute to the reduction of the fossil fuel consumption, as well as the reduction of the environmental impact therein, mainly avoiding methane emissions.